A META ANALYSIS STUDY: DIGITAL APPLICATIONS AS LEARNING MEDIA IN ISLAMIC RELIGIOUS EDUCATION - Tarsono, Tarsono; Nasution, Ahmad Jaelani; Muflihah, Muflihah; Saputri, Septia Nur; Polem, Muhammad; Nurhadianto, Nurhadianto; Ruswandi, Uus (LPPM Universitas PGRI Pontianak, 2024)
This research aimed to examine the effectiveness of digital application-based learning media in enhancing student learning outcomes in PAI subjects. A total of eleven studies were gathered and analyzed through SPSS 27 software. The research methodology employed was Meta-Analysis. Results indicated a notable improvement in learning outcomes, as the highest score before utilizing digital applications was 78.96, and the lowest was 44.69. Following the implementation of digital applications, the highest score rose to 91.84 and the lowest to 81.32. Statistical analyses, including paired sample t-test and correlation test, demonstrated a significant disparity in learning outcomes pre- and post-use digital applications, with a p-value <0.05. The findings suggest that digital applications effectively enhance students' learning outcomes, offering flexibility, interactivity, and appeal that heighten learner engagement.